Trannational Economic Crime Organization: A Threat Of Thailand - et. al., Pongpoj Tammakulvich, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to study patterns of transnational economic crime organizations in Thailand, problem and obstacle to litigate transnational economic crime organizations in Thailand and study measures to enforce the Prevention and Suppression of Involvement in Transnational Criminal Organization Act (2013) with the litigation of transnational economic crime organizations that will lead to the improvement of legal provisions of ASEAN to be under the same standard. The researcher used a qualitative research method which is an individual in-depth interview with 24 key informants who are experts in the justice process with experiences of litigation concerning economic crimes offense, and transnational crime organizations, and conducted an in-depth interview with people who are victims by using an accidental sampling method. The results revealed that factors causing transnational crime organizations in Thailand are caused by modern communication and technology, geographic factors of Thailand, convenient transportations, and tourism policies. Characteristic of transnational economic crime organizations in Thailand are loosely structured and also linked to local crime networks. The major difficulty of litigation of transnational economic crime organizations in Thailand is caused by the lack of international cooperation that is found that most of the law enforcement officials lack both knowledge and understanding of the law regarding transnational economic crime organizations. In addition, the enforcement of Prevention and Suppression of Involvement in Transnational Criminal Organization Act (2013) was found greatly suitable to enforce specific measures to be important machinery to seek evidence and tools in stringent suppression of transnational economic crime organizations.